Cold Weather Injuries: Initial Evaluation and Management. Issue 4 (April 2022) - Vogel, Kendall; Hulsopple, Chad
Abstract : This article discusses the pathophysiology and recommendations for field evaluation and management of cold weather injuries. Abstract: As more people take to extreme sporting activities and hobbies, the sports medicine physician should be proficient in early identification and initial sideline or field management of cold weather injuries. There is significant mortality and morbidity associated with these conditions. The most severe of these are hypothermia and frostbite, which have limited evidence for their field management. Nonfreezing cold injuries and chilblains are much rarer, although appropriate prevention and treatment strategies can be used to minimize harm to athletes. This article will provide the most updated recommendations for field or sideline evaluation and initial management of hypothermia, frostbite, nonfreezing cold injury, and chilblains.